The effects of clinical crown length on the sagittal movement of maxillary central incisor in clear aligner treatment: a finite element exploration - Chen Zhou; Zhicai Feng; Jianhan Ren; Haotian Luo; Hio Cheng Ieong; Runze Li; Yangqiao Qing; Yuqing Guo; Bingyan Guo; Zichun Huang; Yang Cao; Weicai Wang (BMC Oral Health)
Abstract Background The mechanism of force application in clear aligner treatment involves wrapping the clinical crowns, suggesting that the size of the clinical crowns may impact tooth movement. The present finite element study aimed to explore the impact of clinical crown length on the sagittal movement of maxillary central incisor in clear aligner treatment. Methods The standard maxillary dentition model was developed using computer tomography scanning. Finite element models of the maxillary dentition, alveolar bone, periodontal ligament, and aligners were established. Twelve model groups were divided based on different clinical crown lengths and attachments’ position to simulated the tipping and translational movements of the right maxillary central incisor. The dimensions of the short and long clinical crowns were determined based on epidemiological evidence, and appropriate models were constructed by shortening or elongating the normal incisors by 20% along the longitudinal axis of the tooth. Horizontal rectangular attachments were constructed at the clinical crown center of the short, normal and long clinical crowns. These attachments were categorized into four types: no attachment, labial attachment, palatal attachment and labio-palatal attachments. The finite element analysis focused on evaluating the contact pressure distribution on the crown, displacements, rotations, and von Mises stress in PDL of the right maxillary central incisors. Results In tipping movement, the long clinical crown exhibited the highest crown displacement and rotation, enhancing the efficiency. In translational movement, the long clinical crown had the lowest TL/CD value, losing less torque during the crown displacement. However, the short clinical crown had the lowest M x /F y value, with a greater tendency to move bodily rather than long ones. The von Mises stress distribution in PDL was similar between the two types of movement, while the maximum von Mises stress increased with increasing clinical crown lengths in tipping movement. Labio-lingual attachment had the optimal effect in tipping and translational movement. Conclusions Clinical crown length has considerable influences on the efficiency, movement behavior, and maximum von Mises stress of the PDL in the sagittal movement of maxillary center incisor in clear aligner treatment. Moreover, attachments also influence the movement efficiency of the incisor.